Patterns of Magnetic Resonance Imaging and Early Detection via Diffusion-weighted Imaging of Neonatal Hypoxic Brain Injury: A Cross-sectional Study - G Selva Kumar; Pronami Borah; Aukifa Khamim Sabibahul Islam; Shruti Kashyap (Indian Journal of Neonatal Medicine and Research)
Introduction: Hypoxic-ischaemic Encephalopathy (HIE) is caused by a hypoxic or ischaemic event, resulting in hypoxemia and hypercapnia. Magnetic Resonance Imaging (MRI) is the most sensitive and specific imaging technology for newborns with HIE. Diffusion-Weighted Imaging (DWI) can detect ischaemic changes in the first days after birth. Aim: To assess various MRI findings and their distribution patterns in neonates with HIE, as well as the importance of DWI in the early detection of HIE. Materials and Methods: A hospital-based cross-sectional study was performed in the Department of Radiology at Assam Medical College, Dibrugarh, Assam, India over a period of one year, from August 2021 to July 2022. The study included 88 neonates with HIE diagnosed using the Sarnat staging system (stages II and III). The MRI protocol comprised T2-weighted (axial and coronal), T1-weighted (axial), T2 Fluild Attenuated Inversion Recovery (FLAIR) (axial), DWI (axial), Apparent Diffusion Coefficient (ADC) map, and Gradient eco sequences (GRE) (axial). The Analysis of Variance (ANOVA) test or Student’s t-test was used for the association tests for continuous variables, with a p-value <0.05 considered statistically significant. Results: Most babies underwent MRI between 4 and 7 days of life, and the male-to-female ratio was 1.3:1. The MRI patterns observed included deep grey matter injury in 39 (44%), cortical injury in 17 (19.3%), periventricular injury in 11 (12.5%), and a mixed pattern in 21 (23.9%). The most common patterns observed in preterm and term babies were periventricular leukomalacia and central patterns of injury, respectively. DWI detected ischaemic changes in less than seven-day-old neonates (73.7%) before conventional MRI (50.9%) could identify these changes. Conclusion: The MRI offers excellent differentiation between grey and white matter and provides a good depiction of the pattern of myelination. MR-DWI adds sensitivity and provides information not seen in the other conventional sequences. MRI can predict severe brain injury in preterm infants who may exhibit less obvious clinical signs of HIE.